Modulation of Hyperpolarization-Activated Inward Current and Thalamic Activity Modes by Different Cyclic Nucleotides - Datunashvili, Maia; Chaudhary, Rahul; Zobeiri, Mehrnoush; Lüttjohann, Annika; Mergia, Evanthia; Baumann, Arnd; Balfanz, Sabine; Budde, Björn; van Luijtelaar, Gilles; Pape, Hans-Christian; Koesling, Doris; Budde, Thomas (Frontiers in Cellular Neuroscience, 2018)
The hyperpolarization-activated inward current, Ih, plays a key role in the generation of rhythmic activities in thalamocortical relay (TC) neurons. Cyclic nucleotides, like 3’, 5’-cyclic adenosine monophosphate (cAMP), facilitate voltage-dependent activation of HCN channels by shifting the activation curve of Ih to more positive values and thereby terminating the rhythmic burst activity. The role of 3’, 5’- cyclic guanosine monophosphate (cGMP) in modulation of Ih is not well understood. To determine the possible role of the NO-sensitive cGMP-forming guanylyl cyclase 2 (NO-GC2) to the control of thalamic Ih, the voltage-dependency and cGMP/cAMP-sensitivity of Ih was analyzed in TC neurons of the dorsal part of the lateral geniculate nucleus (dLGN) in WT and NO-GC2-deficit (NO-GC2-/-) mice. Whole cell voltage clamp recordings in brain slices revealed a more hyperpolarized half maximal activation (V1/2) of Ih in NO-GC2-/- TC neurons compared to wild type (WT). Different concentrations of 8-Br-cAMP / 8-Br-cGMP induced dose-dependent positive shifts of V1/2 in both strains. Treatment of WT slices with lyase enzyme inhibitors (SQ22536 and ODQ) resulted in further hyperpolarized V1/2. Under current clamp conditions NO-GC2-/- neurons exhibited a reduction in the Ih-dependent voltage sag and reduced action potential firing with hyperpolarizing and depolarizing current steps, respectively. Intrathalamic rhythmic bursting activity in brain slices and in a simplified mathematical model of the thalamic network was reduced in the absence of NO-GC2. In freely behaving NO-GC2-/- mice, delta and theta band activity was enhanced during active wakefulness (AW) and rapid eye movement sleep (REM) in cortical local field potential (LFP) in comparison to WT. These findings indicate that cGMP facilitates Ih activation and contributes to a tonic activity in TC neurons. On the network level basal cGMP production supports fast rhythmic activity in the cortex.